In vitro and in vivo antimicrobial effects of domiphen combined with itraconazole against Aspergillus fumigatus - Yang, Huan; Gu, Yufan; He, Zhiqiang; Wu, Jia-Nan; Wu, Chen; Xie, Yuhan; You, Yuxin; Yang, Yijia; Zhou, Xinyu; Liu, Yi; Du, Wenlong (Frontiers in Microbiology, 2023)
Aspergillus fumigatus, a prevalent saprophytic fungus in the atmosphere, is known to rapidly induce severe invasive aspergillosis (IA) upon inhalation of its conidia by humans or animals. The mortality rate associated with IA exceeds 50%. The misuse of antifungal agents has contributed to the emergence of numerous highly pathogenic drug-resistant strains of A. fumigatus. Our study found that the combination of domiphen and itraconazole had sound synergistic antimicrobial effects against wild-type and itraconazole-resistant A. fumigatus in vivo and in vitro through MIC, FICI, plate inoculation, growth curve experiments, and Galleria mellonella infection model. Drug cytotoxicity and pharmacological tests for acute toxicity assays demonstrated that both itraconazole and domiphen showed minimal cytotoxicity and good biocompatibility. The transcriptome sequencing experiment demonstrated that domiphen exerted a suppressive effect on the expression of various genes, including those involved in drug efflux, redox regulation, and cellular membrane and cell wall remodeling.The present investigation explores the synergistic antimicrobial mechanisms of domiphen and itraconazole, encompassing three key aspects: (i) domiphen inhibited the efflux of itraconazole by reducing the expression of drug efflux-related genes, (ii) the combination has good ability to disrupt the cell membrane and cell wall, (iii) the combination also can remove biofilm more effectively. In summary, the utilization of domiphen as a synergist of itraconazole exhibited disruptive effects on the biofilm, cell wall, and cell membrane of A. fumigatus. This subsequently led to a modified distribution of itraconazole within the fungal organism, ultimately resulting in enhanced antifungal efficacy. The results of this study may provide a new therapeutic strategy for the treatment of IA caused by drug-resistant A. fumigatus.